TEXNOLOGIYA SABAQLARÍNDA KLASSTAN TÍS JUMISLARDÍ SHÓLKEMLESTIRIW HÁM ÓTKERIWDIŃ AYÍRÍM MÁSELELERI - Tańbaev, N. (SCIENCE and SOCIETY, 2021)
In this article, we will talk about the methods of organizing and conducting extracurricular activities in the lessons of Technology. In the development of extracurricular activities, the importance of extracurricular activities in the development of activities, creative and creative thinking of students, including the types of procedures for carrying out extracurricular activities, the strict conditions in which they are obliged to comply, the psycho-physiologic conditions of students, the sense of respect for themselves, the ability to evaluate themselves.